Pengaruh Literasi Keuangan Syariah terhadap Minat Masyarakat Menjadi Nasabah pada Bank Muamalat - Eki Nur Bia; Eko Nursalim; Zanuar Anwari (Ahsan: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
This study aims to analyze the influence of Islamic financial literacy on people's interest in becoming customers at Bank Muamalat, Sangatta Utara District, East Kutai Regency. Islamic financial literacy is defined as people's understanding of financial principles in accordance with Islamic sharia, including knowledge of Islamic financial products and how to manage finances well. This study uses a quantitative approach with a data collection method through a questionnaire distributed to 50 respondents. The results of the study indicate that Islamic financial literacy has a positive and significant influence on people's interest in becoming customers. The simple linear regression test produces a regression coefficient of 0.823, which indicates that every one-scale increase in Islamic financial literacy will increase people's interest in becoming customers. In addition, the results of the T and F tests show that Islamic financial literacy has a significant effect on interest in becoming customers with a significance value of 0.000.